Sonolysis in Prevention of Brain Infarction During Carotid Endarterectomy and Stenting (SONOBUSTER): a randomized, controlled trial - Školoudík, David; Kuliha, Martin; Hrbáč, Tomáš; Jonszta, Tomáš; Herzig, Roman; SONOBUSTER Trial Group (European heart journal, 2016)
AIMS: Previous case series have detected silent brain infarctions in as many as one-third of patients after carotid endarterectomy (CEA) and in up to two-thirds of patients after carotid angioplasty and stenting (CAS). Sonolysis employs ultrasound to facilitate disruption of thrombi and has been shown to be safe and effective for improving long-term outcomes following acute stroke. Here, we examined whether intraoperative sonolysis alters the risk of new brain ischaemic lesions during CEA or CAS. METHODS AND RESULTS: All consecutive patients with internal carotid stenosis ≥70% indicated for CEA/CAS were screened in this prospective study. Patients were allocated randomly to sonolysis and control groups. Neurological examination, cognitive function tests, and brain magnetic resonance imaging (MRI) were conducted before intervention and at 24 and 30 days post-surgery. Of the 487 screened patients, 121 (87 males; mean age, 66.65 ± 7.17 years) were allocated to the sonolysis group and 121 (75; 66.02 ± 8.11 years) to the control group. New brain ischaemic lesions on post-procedure MRI were significantly less frequent in the sonolysis group than in the control group (31.4% of patients vs. 47.1%; P = 0.018). Sonolysis and CEA were identified as independent predictors of reduced brain ischaemic risk [sonolysis: odds ratio (OR) = 0.450 (0.215-0.942), P = 0.034 and CEA: OR = 0.208 (0.087-0.495), P < 0.001]. Stroke or transient ischaemic attack occurred in one sonolysis patient and three control patients (P = 0.372). No significant group differences were found in post-intervention cognitive test scores (P > 0.3). CONCLUSION: This study provides Class II evidence that sonolysis during CEA or CAS reduces the risk of new brain ischaemic lesions. CLINICAL TRIAL REGISTRATION: http://www.clinicaltrials.gov (NCT01591005).
Keywords: Male; karotická endarterektomie; Stents; Brain infarction; Prospective Studies; Humans; Carotid Stenosis; Endarterectomy; senioři; Stenting; stenty; prospektivní studie; mužské pohlaví; Female; stenóza arteria carotis; angioplastika; Aged; Endarterectomy, Carotid; Brain Infarction; Sonolysis; ženské pohlaví; Angioplasty; lidé; mozkový infarkt